Effect of Chitosan-Coated Centella asiatica Nanoparticles on Kidney Histology Profile of Complicated Diabetic Mice - Muchtaromah, Bayyinatul; Firdaus, Ana Mar'a Konita; Minarno, Eko Budi; Fitriasari, Prilya Dewi; Rhomawati, Mei; Duhita, Maharani Retna; Putra, Wira Eka (UIN Sunan Gunung Djati Bandung, 2023)
Gotu kola (Centella asiatica) is a medicinal plant that has potential as an antioxidant and antidiabetic. Its compound is able to protect against diabetic nephropathy through the inhibition of oxidative stress. In terms of increasing drug potency and bioavailability of C. asiatica compounds, nanoparticle technology was used. This study aimed to determine the effect of C. asiatica nanoparticles coated with chitosan on the renal histology profile of complicated diabetic mice using a completely randomized design (CRD) with five treatment groups and five replications. The treatment groups were divided into K- (the experimental animals were not given any treatment), K+ (the experimental animals were induced by STZ), P1 (STZ + C. asiatica nanoparticles 120 mg/kgBW), P2 (STZ + C. asiatica nanoparticles 180 mg/kgBW), P3 (STZ + C. asiatica nanoparticles 240 mg/kgBW). The experimental animal model of complicated diabetes was induced by intraperitoneal STZ at a dose of 40 mg/kgBW for two days and STZ at a dose of 60 mg/kgBW for three days and then left for nine days. The C. asiatica nanoparticle therapy was given for 28 days. The parameters in this study were the results of scoring cell damage in the glomerular and tubular tissues (proximal and distal) of the kidney. The data obtained were tested for normality and homogeneity, then the normal and homogeneous data were tested with one-way ANOVA and further tested with Duncan's test. The statistical analysis results showed that C. asiatica coated with chitosan nanoparticles could reduce the damage to the histological profile of the glomerulus and tubules (proximal and distal) of the kidney of diabetic mice. C. asiatica-coated nanoparticles at a dose of 240 mg/kgBW showed the most optimal reduction in damage to the glomerular and tubular histology profiles.